(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
During the last ten years, electric vehicles have become more and more part of daily mobility. Supported by different policies, but also by technological advances, electromobility is far to be an achieved topic and is entering a new decade. Hybrid solutions continue to offer an alternative using combustion engines. Latest researches and developments on fuel cells push to an alternative future, based on hydrogen. Electric batteries, as energy storage on vehicles, remain the most important way to conduct EVs to the roads, with regular improvements. All these technologies are developing solutions to provide and control the energy for an electric motor. The classic solution using one engine and a kinematic chain to distribute the mechanical power to the wheels is completed by the possibility of integrating not only one but more electric motors in the same vehicle.